CHARACTERISTICS OF SINABUNG VOLCANIC EARTHQUAKE IN DECEMBER 2013 USING SPECTRAL ANALYSIS - HARTONO (NIM : 12313048), KEVIN
Sinabung is a strato-type volcano located in Karo District, North Sumatera Province, Indonesia. It is considered as A-type volcano after the first eruption—after more than 400 years of quiescence— occurred in 2010, and reactivated again in 2013. The eruption started with a phreatic phase, changed to phreatomagmatic, and then effusive eruption which had formed lava dome at the summit crater in late December 2013. Increased volcanic activity in Sinabung can be characterized by the emergence of volcanic seismicity recorded in seismograms nearby. Event classification has been done on the seismograms in Sinabung observatory station to determine the type of earthquake and to link it with the possible source mechanism. The seismogram data were acquired from Center of Volcanology and Geological Hazard Mitigation (CVGHM) for the period of December 2013. The classification was done by viewing the seismogram per 1 minute, and spectral analysis with Short-Time Fourier Transform (STFT) was applied to unidentifiable signals to obtain the frequency content. The result of the classification shows the type of volcanic seismicity recorded in Sinabung Volcano during the December 2013 period are volcanic-tectonic A (VTA), volcanic-tectonic B (VTB), low frequency (LF), hybrid, volcanic tremor, rockfall, and tectonic. The characteristic of VTA and VTB earthquake showed a similar high frequency content (10-18 Hz and 9-16 Hz respectively) and can only be distinguished by the onset of P and S wave. High frequency signal was found at the onset of LF earthquakes in this period, although overall the signal itself had a low frequency content. The highlighted feature of this period is the dominance of low frequency and hybrid seismicity from the mid until the end of December that acts as a precursor to the lava dome growth process in Sinabung Volcano. VTA seismicity occurred in relatively high intensity at the beginning and the end of December, indicating the continuation of magma migration to the lower crustal chamber. LF and hybrid seismicity impulsively and repetitively emerged in high intensity during the dome growth phase. We have also found the domination of hybrid seismicity in the middle of the period that changed into the rise of LF seismicity after 18 December, the day that Sinabung’s lava dome was first observed.